Screening of promoted CeO2/Al2O3 catalysts in aqueous phase glycerol reforming and hydrogenolysis into 1,2-propanediol - Azri, Norsahida; Irmawati, Ramli; Leong, Rudy Hakim Danial; Nda-Umar, Usman Idris; Saiman, Mohd Izham; Taufiq-Yap, Yun Hin; Abdulkareem-Alsultan, G. (Malaysian Society of Analytical Sciences, 2024)
A series of promoted CeO2/Al2O3 catalysts (10Cu-90CeO2/Al2O3, 10Ni-90CeO2/Al2O3, 10Co-90CeO2/Al2O3) were synthesized via method of impregnation and later calcined at 600 ℃. Those catalysts were formerly tested for their physicochemical properties by X-ray diffraction (XRD), H2-temperature programmed reduction (H2-TPR), and NH3-temperature programmed desorption (NH3–TPD). After characterized, it was then evaluated in the performance of catalytic glycerol conversion into 1,2-propanediol; propylene glycol (1,2-PDO; PG) via aqueous phase glycerol reforming and hydrogenolysis route under inert N2 flow. Among the examined catalysts, CeO2/Al2O3 with 10wt% Cu loading (10Cu-90CeO2/Al2O3) showed optimum catalytic activity with 88.5% glycerol conversion (GC) and 35.5% PG selectivity at 300 ℃ reaction temperature, 2 h duration test, 30 cc/min of N2 initial pressure, 0.1 g catalyst dosage and 10wt% glycerol concentration. The high catalytic performance of 10Cu90CeO2/Al2O3 was owing to the good copper-cerium-alumina interaction via its good metal reducibility at low temperature along with good acid capacity for the reaction.